A produção científica no CAPPA/UFSM: artigos científicos em língua inglesa sob a perspectiva da análise crítica de gênero - Cervo, Nathieli Cipolat (2023)
Paleontology is the science which studies living beings and organisms that inhabited Earth in the past, in order to understand the evolutionary process of species and the probable relations amongst them. In the Brazilian state of Rio Grande do Sul, the Support Center for Paleontological Research from the Fourth Colony, also known as CAPPA, is connected to the Federal University of Santa Maria (UFSM). CAPPA is mainly acknowledged for discovering the most ancient fossil records of dinosaurs in the world, located in the central region of the State. In this sense, the present study aims at investigating the academic articles written in English and published by the members of CAPPA, focusing on the rhetorical organization of Introduction sections and on the structure and the representation of these articles’ titles. The corpus was collected in loco during a semi structured interview with the current director of CAPPA. Subsequently, the corpus was narrowed down to 22 samples of scientific articles written in English and published by CAPPA’s staff members from 2015 to 2022. The samples were investigated under the perspective of Motta-Roth’s (2008) Critical Genre Analysis (CGA), and the dimensions of context and text were both analyzed. Thereby, CAPPA constitutes a discursive community, the academic article is the discursive genre that prevails in their scientific productions and its objective is to report paleontological discoveries to the scientific community. In general, the academic articles are produced by CAPPA’s paleontologists, with occasional contributions from researchers external to UFSM, they are published in interdisciplinary foreign journals, and they are targeted at other paleontologists, scientists from similar areas and researchers in training. Besides, the investigated samples not only follow a common organization of the discursive genre, but also present variations in the general structure of the text, following the IMRD scheme, and in the rhetorical organization of the Introduction sections, fitting the CARS model (SWALES; FEAK, 2012). Moreover, results suggest that there is a significant preference for the use of non-integral citations, and that CAPPA’s researchers tend to direct the focus to the referenced research. Lastly, the title analysis showed that there is also a clear preference for short and objective titles and for nominalizations (Ibidem; RAVELLI, 1988; HALLIDAY; MATTHIESEN, 2014), which suggests a title format that instigates the reader and turns the meaning construction more complex in titles. We hope the current research contributes for Applied Linguistics studies, as well as for CGA and English for Academic Purposes, and the results presented here promote critical reflections on the academic writing process in English and on the disciplinary linguistic variations in scientific articles.